Assessment of nutritional status of adolescent girls from 15-18 years in private high schools in Raipur, Chhattisgarh - Dr. Sharja Phuljhele; Dr. Prankur Pandey; Dr. Prerana Singh (Pediatric Review: International Journal of Pediatric Research, 2021)
Background: Adolescent period is a phase of human development comprising the change from childhood to adulthood. Nutritional requirements increase to a great extent during this period as compared to the previous years of growth. Adolescence may represent a window of opportunity to prepare nutritionally for healthy adult life. The present study was intended to assess the nutritional status of school-going adolescent girls.Materials and Methods: This one-year community-based, cross-sectional study was conducted in private high schools in an urban area of Raipur, Chhattisgarh among 480 adolescent girls of 15-18 years. All the selected adolescent girls were personally interviewed with the help of a pre-designed and pre-tested questionnaire regarding age, type of family, dietary habits and socioeconomic status. A three-day recall method was used to assess nutrient intake. The nutrient intake was calculated using tables of nutritive value of Indian foods.Results: As per WHO nutritional measurement criteria, children were classified as per their anthropometric criteria as, 31.46% had moderate stunting and 4.38% were severely stunted. 2.71% had severe thinness, 27.92% were thin and 7.71% were overweight. The major morbidity among study subjects was, 19.6% had conjunctival pallor(anaemia), 8.75% had dental caries, 6.46% had Vitamin B complex deficiency, 4.8% had angular stomatitis and 0.84% had Vitamin A deficiency.Conclusion: The present study recommends that efforts should be made to reduce the prevalence of malnutrition among adolescent girls. For this regular health check-ups should be done at schools with the help of school authorities and hospitals.